New Therapeutic Targets in Antineutrophil Cytoplasm Antibody–Associated Vasculitis. Issue 3 (3rd February 2021) - Prendecki, Maria; McAdoo, Stephen P.
Abstract : Antineutrophil cytoplasm antibody (ANCA)–associated vasculitis (AAV) is a rare systemic autoimmune disease that is characterized by necrotizing inflammation of predominantly the small blood vessels and the presence of circulating ANCAs directed against myeloperoxidase or proteinase 3. Current treatment strategies for severe disease, supported by the findings of several well‐coordinated randomized controlled trials, aim to induce remission with high‐dose glucocorticoids and either rituximab or cyclophosphamide, followed by relapse prevention with a period of sustained low‐dose treatment. This approach has dramatically improved outcomes in AAV; however, a significant proportion of patients develop serious treatment‐related side effects or experience relapse. Recent advances in our understanding of the pathogenesis of AAV have led to the identification of novel therapeutic targets that may address these problems, including strategies directed at the aberrant adaptive autoimmune response (B and T cell–directed treatments) and those targeting innate immune elements (complement, monocytes, and neutrophils). It is anticipated that these novel treatments, used alone or in combination, will lead to more effective and less toxic treatment regimens for patients with AAV.